New benefit-sharing principles for digital sequence information - Halewood, Michael; Bagley, Margo A.; Wyss, Markus; Hartmann Scholz, Amber (American Association for the Advancement of Science, 2023)
Since 1992, international laws governing access and benefit sharing (ABS) have confirmed the principle that countries have sovereign rights over their nonhuman biological diversity and can regulate access to their genetic resources. These laws require the fair and equitable sharing of monetary (e.g., royalties) and nonmonetary (e.g., scientific training) benefits resulting from physical access to and utilization of those genetic resources (GRs). The Kunming-Montreal Global Biodiversity Framework, adopted by the Conference of the Parties to the Convention on Biological Diversity (CBD) at their 15th meeting (COP-15) in December 2022 (1), includes a decision to establish a separate, multilateral benefit-sharing mechanism for the use of “digital sequence information” (DSI), i.e., biological data associated with, or derived from, genetic resources such as nucleotide sequences and epigenetic, protein, and metabolite data. The international community has a narrow window of opportunity to develop a DSI benefit-sharing framework that is simple, harmonized, effective, and transformational.